Economic and Social Survey of Asia and the Pacific 2024 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2024)
Given the urgency of the SDG Stimulus and that public debt distress is likely to remain a major macroeconomic policy challenge for Asia and the Pacific in coming years, the Survey 2024 will continue to focus on fiscal and public debt challenges and policy options. After outlining the changing economic, financial and development context and its medium-term fiscal implications, the Survey 2024 will dive deeper into policy options that developing Asia-Pacific economies, as debtors and as part of the international community, can explore to boost affordable and long-term financing for essential public spending on sustainable development and reduce the associated sovereign credit risks and costs. In addition to identifying ‘what’ policy actions should be taken, the Survey 2024 will also give emphasis on ‘how to’ implement the needed policy actions. Insights from approaches such as political economy, behavioural science, and country case studies will be used.